Three Bacterial DedA Subfamilies with Distinct Functions and Phylogenetic Distribution - Horia Todor; Nadia Herrera; Carol A. Gross (mBio, 2023)
ABSTRACT Recent studies in bacteria have suggested that the broadly conserved but enigmatic DedA proteins function as undecaprenyl-phosphate (UndP) flippases, recycling this essential lipid carrier. To determine whether all DedA proteins have UndP flippase activity, we performed a phylogenetic analysis and correlated our findings to previously published experimental results and predicted structures. We uncovered three major DedA subfamilies: one contains UndP flippases, the second contains putative phospholipid flippases and is associated with aerobic metabolism, and the third is found only in specific Gram-negative phyla. IMPORTANCE DedA family proteins are highly conserved and nearly ubiquitous integral membrane proteins found in archaea, bacteria, and eukaryotes. Recent work revealed that eukaryotic DedA proteins are phospholipid scramblases and that some bacterial DedA proteins are undecaprenyl phosphate flippases. We performed a phylogenetic analysis of this protein family in bacteria that revealed 3 DedA subfamilies with distinct phylogenetic distributions, genomic contexts, and putative functions. Our bioinformatic analysis lays the groundwork for future experimental studies on the role of DedA proteins in maintaining and modifying the membrane.